Analyzing the interactions of mRNAs, miRNAs and lncRNAs to predict ceRNA networks in bovine cystic follicular granulosa cells - Wang, Kai; Cheng, Ying; Guo, Tong; Guo, Xiangqian; Zhang, Hongzhi; Ma, Xiaoyan; Pan, Yangyang; Kebreab, Ermias; Wang, Dong; Lyu, Lihua (Frontiers in Veterinary Science, 2022)
Cross-talk between competitive endogenous RNAs (ceRNAs) may play a critical role in revealing potential mechanism of bovine follicular cysts. Ovarian cyst has always been an intractable scientific problem and has led to considerable economic losses to bovine breeding industry. However, its pathogenesis and molecular mechanisms are still not well understood. Here, this study aimed to investigate the role of non-coding RNAs (ncRNAs) and the ceRNA networks in bovine follicular cyst. Whole transcriptome sequencing of bovine follicular granulosa cells (GCs) was conducted to obtain the expression profiles of mRNAs, lncRNAs and miRNAs. The results for the identified expressions of 8,003 mRNAs, 579 lncRNAs and 205 miRNAs were often altered between cystic and normal follicular GCs. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses were performed on these differentially expressed mRNAs. Furthermore, the ceRNA network combining mRNAs, miRNAs, and lncRNAs using several bioinformatics methods based on co-expression analysis between the differentially expressed RNAs was conducted. Finally, the lncRNA NONBTAT027373.1-miR-664b-HSD17B7 pathway was verified by dual-luciferase reporting assay and RNA binding protein immunoprecipitation (RIP) assay. LncRNA NONBTAT027373.1 sponged miR-664b in GCs and prevented miR-664b from binding to the HSD17B7 3′-UTR. These results indicated that genes and lncRNAs related to steroid hormone synthesis and energy metabolism could play important roles in the formation of bovine cystic follicles through the ceRNA mechanism and represent candidate targets for further research. This can be used as a practical guideline for promoting healthy and highly efficient development in the bovine industry.